Dose–response effectiveness of focused shockwave therapy on ultrasonographic muscular properties in patients with stroke exhibiting ankle spasticity - Yang, Shu-Mei; Lin, Hung-Hsi; Chen, Yen-Hua; Lu, You-Lin; Wu, Chueh-Hung; Chen, Wen-Shiang; Lin, Meng-Ting (Journal of neuroengineering and rehabilitation, 2025)
Background Post-stroke spasticity (PSS) in the ankle plantar flexors leads to abnormal gait, increased energy expenditure, and a higher risk of falls. Ultrasonographic measures, such as muscle fascicle length (MFL) and pennation angle (PA), provide insight into muscle changes associated with spasticity. This study aimed to investigate the dose-dependent effects of focused extracorporeal shockwave therapy (ESWT) on ultrasonographic muscle properties and clinical outcomes in patients with PSS of the ankle plantar flexors. Methods This post hoc analysis was based on a double-blind, randomized controlled trial investigating different ESWT doses for post-stroke ankle spasticity treatment. A total of 39 patients with PSS of the ankle plantar flexors were randomized into two groups: the double-dose ESWT group received 4,000 focused shockwave pulses per session, while the control ESWT group received 2,000 pulses per session. Both groups received four ESWT sessions over a two-week intervention period, followed by a 24-week follow-up period for outcome assessments. Outcome measures included ultrasonographic assessments of MFL, PA, and strain elastography, as well as clinical evaluations using the Modified Ashworth Scale (MAS), Modified Tardieu Scale (MTS), passive range of motion (PROM), Timed Up and Go (TUG) test, and Barthel Index at baseline, and at 1, 4, 12, and 24 weeks post-treatment. Results No significant within-group changes in PA or MFL were observed for either ESWT group over the 24-week period. Generalized estimation equation analysis showed no significant group effects on PA, MFL, or strain elastography. However, when analyzing all participants, a significant time-related improvement in MFL was identified. In the double-dose ESWT group, MFL was significantly correlated with MTS, PROM, and TUG test, while PA was significantly correlated with MAS. Given that this was a post hoc analysis, these results should be interpreted conservatively. Conclusions While PA and MFL did not show significant differences between groups, the double-dose ESWT group exhibited improved clinical outcomes linked to MFL. These findings suggest that increased ESWT dosage may enhance muscle architecture and function in stroke rehabilitation.